Global economic justice in the face of a return to the economy of the great depression - Cortés Rodas, Francisco (Estudios de Filosofía, 2010)
This article criticizes some of the Theoretical Proposals for Global Justice because they are not able to point out alternatives which will enable us to overcome the pressing problems of world poverty and the increase of the inequalities of the contemporary world. The central criticism points out that the Proposals for Global Justice, such as Rawls`, Habermas` or Pogge`s, are insuf cient inasmuch as they reduce the Problem of Justice to a merely re-distributive matter. By restricting the Problem of Justice to a Fair Distribution of Goods without bearing in mind the causes that determine social inequalities and the structural asymmetricalities in the relations of power of the contemporary capitalist order, the Theories of Global Justice end up af rming the fundamental principles of the ruling domination system. To base these ideas, the authors take their bearings in the literature that Michel Aglietta, Laurent Berrebi, Joseph Stiglitz, Paul Krugman and the authors of the French Regulationist School have been producing about the crisis of Capitalism.